All roads lead to Rome: the plasticity of gut microbiome drives the extensive adaptation of the Yarkand toad-headed agama (Phrynocephalus axillaris) to different altitudes - Du, Jianghao; Zheng, Peng; Gao, Weizhen; Liang, Qianru; Leng, Lin; Shi, Lei (Frontiers in microbiology, 2025)
The gut microbiome was involved in a variety of physiological processes and played a key role in host environmental adaptation. However, the mechanisms of their response to altitudinal environmental changes remain unclear. In this study, we used 16S rRNA sequencing and LC-MS metabolomics to investigate the changes in the gut microbiome and metabolism of the Yarkand toad-headed agama ( Phrynocephalus axillaris ) at different altitudes (−80 m to 2000 m). The results demonstrated that Firmicutes, Bacteroidetes, and Proteobacteria were the dominant phylum, Lachnospiraceae and Oscillospiraceae were the most abundant family, and the low-altitude populations had higher richness than high-altitude populations; Akkermansiaceae appeared to be enriched in high-altitude populations and the relative abundance tended to increase with altitude. The gut microbiome of three populations of P. axillaris at different altitudes was clustered into two different enterotypes, low-altitude populations and high-altitude populations shared an enterotype dominated by Akkermansia , Kineothrix , Phocaeicola ; intermediate-altitude populations had an enterotype dominated by Mesorhizobium , Bradyrhizobium . Metabolites involved in amino acid and lipid metabolism differed significantly at different altitudes. The above results suggest that gut microbiome plasticity drives the extensive adaptation of P. axillaris to multi-stress caused by different altitudes. With global warming, recognizing the adaptive capacity of wide-ranging species to altitude can help plan future conservation strategies.